Crisis de basura en la Tierra - Stadler, Alexander (New York : Scholastic, 2008)
A los ocho anos de edad, Julian Rodriguez escapa de la pena del castigo, imaginadose como un guerrero del espacio exterior.
Eight-year-old Julian Rodriguez escapes from the crisis of the moment (being sent to his room for not taking out the trash) by imagining he is a space warrior.
Keywords: Conduct of life -- Juvenile fiction; Imagination -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Humorous stories -- Juvenile literature; Humorismo -- Literatura juvenil; Conducta (Etica) -- Novela juvenil; Imaginacion -- Novela juvenil; Seres extraterrestres -- Novela juvenil